Challenges for agricultural education and training (AET) institutions in preparing growing student populations for productive careers in the agri-food system. Issue 2 (16th November 2015) - Minde, Isaac; Terblanche, Stephanus; Bashaasha, Bernard; Madakadze, Ignacio Casper; Snyder, Jason; Mugisha, Anthony
Abstract : Purpose: – Agricultural education and training (AET) institutions will play a strategic role in helping to prepare Africa's rapidly growing youth populations for productive careers in agriculture and related agri-businesses. The purpose of this paper is to examine the magnitude of skills and youth employment needs emanating from high-population growth rates. It then explores how agricultural education institutions are responding to these challenges in four different countries at different levels of food system development: South Africa tier 1, Tanzania in tier 2 and Malawi and Uganda in tier 3. Design/methodology/approach: – Demographic and school enrollment data provide information on the magnitude of job market entrants at different levels of education while Living Standards Measurement Studies in the respective countries provide a snapshot of current skill requirements in different segments of the agri-food system. In order to evaluate AET responses, the authors have conducted country-level reviews of AET systems as well as in-depth assessments at key tertiary AET institutions in each of the four case study countries. Findings: – Growth rates in primary school enrollments are high in sub-Saharan Africa. At the same time, because of budgetary constraints, transition rates decline rapidly – about 40 percent from primary to secondary and 7 percent from secondary to tertiary. As a result, substantial numbers of primary and secondary school graduates seek jobs. Research limitations/implications: – The case study countries are limited to four. Had more financial resources and time been available, researchers could have spread further afield and in so doing increasing the precision of the results. Originality/value: – Estimation of the number of primary and secondary school leavers seeking employment because of failure to proceed to the next level of education. Estimation of the level of education shares in the various components of the agri-food system.